Penerapan Model UTAUT Terhadap Penggunaan Media Sosial Instagram di Lingkungan Remaja Kelurahan Cipayung Jakarta Timur - Repiyana Repiyana (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
The Unified Theory of Acceptance and Use of Technology (UTAUT) model has been widely used to study user behavior towards information technology. However, do teenagers understand or not that there is already a UTAUT model that explains the behavior of information technology users. So, the focus of this research is how the application of the UTAUT model to the use of Instagram social media in the Cipayung Village Youth environment. The research method used in this research is Phenomenology with a descriptive qualitative research approach and data collection methods through semi-structured interviews. The results of the study are as follows, first the use of Instagram social media is used as a medium of information, communication, learning, promotion, expanding friendships and increasing creativity. This result is in accordance with performance expectancy. Second, teenagers feel helped by the conveniences provided by Instagram, such as easy to learn applications, easy to use features and teenagers can access information easily. This result is in accordance with Effort Expectancy. Third, the use of Instagram among teenagers in Cipayung Village is influenced by friends, themselves and fear of missing trends, this is in accordance with Social Influence. Fourth, teenagers in Cipayung Village have understanding and knowledge as well as devices such as smartphones or laptops to use Instagram, in accordance with Facilitating Conditions